Quantum mechanics and the covariance of physical laws in quantum reference frames - Flaminia Giacomini (Nature Portfolio, 2019)
Reference frames are ultimately physical systems, and thus it should be possible to quantise them in a consistent way. Here, the authors use a relational formalism to quantise a reference frame and show the covariance of physical laws under transformations between such quantum reference frames.